PERAN BAZNAS DALAM PENDISTRIBUSIAN ZAKAT DI KABUPATEN SIDENRENG RAPPANG - Imran Burhanuddin; Ahmad Mustanir; Erfina Erfina; Muhammad Rais Rahmat Razak (LPPM Universitas Abdurrab, 2026)
This study analyzes the role of the National Amil Zakat Agency (BAZNAS) of Sidenreng Rappang Regency in distributing zakat, both consumptively and productively. The issues raised are the low effectiveness of zakat institutions in carrying out comprehensive and well-targeted distributional functions, as well as the still dominant consumptive distribution pattern that has not yet addressed the structural root causes of poverty. This study employs a descriptive qualitative approach focusing on BAZNAS's role as motivator, facilitator, and mobilizer. Data were collected through in-depth interviews, observation, and documentation with key informants including the BAZNAS Chairman, distribution staff, mustahik (zakat recipients), and community leaders. The research findings indicate that BAZNAS Sidrap has effectively performed these three roles through continuous socialization, needs-based verification mechanisms, and cross-sector collaboration. Supporting factors include local government support, public trust, professional amil (zakat officers), and the utilization of digital technology. Meanwhile, inhibiting factors include limited human resources, minimal operational funds, low zakat literacy, and suboptimal business mentoring. This study recommends strengthening institutional capacity through amil training, digitalization of data systems, and expanding partnerships with the private sector to enhance the effectiveness of productive zakat. This study provides policy implications for local governments in strengthening the regulatory framework for zakat management through the allocation of a special budget for strengthening the institutional capacity of BAZNAS, improving the competence of amil through continuous training programs, and integrating productive zakat programs into the regional poverty alleviation system as part of a social-economic development strategy based on justice.